Oral Administration of Penicillin or Streptomycin May Alter Serum Serotonin Level and Intestinal Motility via Different Mechanisms - Zhu, Cuihong; Gong, Huashan; Luo, Ping; Dong, Li; Zhang, Guohua; Shi, Xueyin; Rong, Weifang (Frontiers in Physiology, 2020)
Background/Aims Enterochromaffin cells (EC cells) constitute the largest population of enteroendocrine cells and release serotonin (5-HT) in response to mechanical and chemical cues of the gastrointestinal tract (GIT). How EC cells respond to altered microbiota such as due to antibiotic treatments remain poorly understood. We hypothesized that the pacemaker channel HCN2 might contribute to the regulation of EC cells functions and their responses to antibiotics-induced changes in intestinal flora. Methods Mice were given either penicillin or streptomycin or both in drinking water for 10 consecutive days. The changes in the profile of short chain fatty acids (SCFAs) in the cecum following penicillin or streptomycin treatments were tested by GC-MS. Serum 5-HT content, whole intestinal transit time, fecal water content, cecum weight and expression of HCN2 and TPH1 in cecal epithelium were measured. Ivabradine (Iva, a HCN channels blocker) was used to explore the role of HCN2 in penicillin-induced changes in 5-HT availability and intestinal motility. Results HCN2 immunofluorescence was detected on intestinal EC cells. Both penicillin and streptomycin caused significant reduction in total SCFAs in the cecum, with the penicillin-treated group showing greater reductions in butyrate, isobutyrate and isovalerate levels than the streptomycin group. The expression of HCN2 was increased in the mice treated with penicillin, whereas TPH1 expression was increased in the mice treated with streptomycin. Mice treated with antibiotics all had larger and heavier cecum, elevated serum 5-HT level and increased fecal water content. Besides, mice treated with penicillin had prolonged intestinal transit time. Intraperitoneal injection of Ivabradine significantly attenuated the effect of penicillin on serum 5-HT level, cecum size and weight, intestinal motility and fecal water content. Conclusions Disruptions of the intestinal flora structure due to oral administration of penicillin may significantly increase serum 5-HT level and inhibit intestinal motility, at least partially through up-regulating the expression of HCN2. Oral administration of streptomycin may alter 5-HT availability by up-regulating TPH1 expression thus increasing synthesis of 5-HT. Alterations of intestinal flora composition due to exposure to different antibiotics may regulate 5-HT availability through different mechanisms.